University library indoor environment quality and student achievement: mediating role of learning engagement - Lingbing Xie; Safial Aqbar Zakaria (International Journal of Evaluation and Research in Education (IJERE), 2026)
This current study investigates how university library indoor environment quality (IEQ) influences academic achievement (AA) through learning engagement (LE), drawing on environmental psychology and learning space theory. Although IEQ has been widely studied in classroom contexts, little empirical evidence exists regarding its academic influence in university libraries, which represent critical yet understudied learning environments. Using survey data from 383 Chinese college students, the study demonstrates that IEQ positively predicts both LE and AA, and that engagement serves as a significant mediating mechanism. These findings highlight the academic value of improving acoustic comfort (AC), visual comfort (VC), thermal comfort (TC), and indoor air quality (IAQ) in library spaces, offering actionable guidance for educational planners seeking to enhance student performance through spatial design. The study contributes novel evidence to the literature on learning environments and suggests future research should incorporate multi-campus samples, broader achievement metrics, and contextual factors to deepen understanding of how environmental conditions shape student learning.